Seed Activism Patent Politics and Litigation in the Global South - Peschard, Karine E. (Food, Health, and the Environment, 2022)
How lawsuits around intellectual property in Brazil and India are impacting the patentability of plants and seeds, farmers' rights, and the public interest. Over the past decade, legal challenges have arisen in the Global South over patents on genetically modified crops. In this ethnographic study, Karine E. Peschard explores the effects of these disputes on people's lives, while uncovering the role of power-material, institutional, and discursive-in shaping laws and legal systems. The expansion of corporate intellectual property (IP), she shows, negatively impacts farmers' rights and, by extension, the right to food, since small farms produce the bulk of food for domestic consumption. Peschard sees emerging a new legal common sense concerning the patentability of plant-related inventions, as well as a balance among IP, farmers' rights, and the public interest. Peschard examines the strengthening of IP regimes for plant varieties, the consolidation of the global biotech industry, the erosion of agrobiodiversity, and farmers' dispossession. She shows how litigants question the legality of patents and private IP systems implemented by Monsanto for royalties on three genetically modified crop varieties, Roundup Ready soybean in Brazil and Bt cotton and Bt eggplant in India. Peschard argues that these private IP systems have rendered moot domestic legislation on plant variety protection and farmers' rights. This unprecedented level of corporate concentration in such a vital sector raises concerns over the erosion of agricultural biodiversity, farmers' rights and livelihoods, food security, and, ultimately, the merits of extending IP rights to higher life forms such as plants.